Strengthening Hajj Governance in Indonesia: Regulatory Challenges, Implementation Gaps, and Consumer Protection Strategies - Muchammad Shidqon Prabowo (Research Horizon, 2026)
Hajj, as one of the pillars of Islam, holds significant religious and social significance for Indonesian Muslims, yet its governance faces complex challenges related to regulation, health, finance, and pilgrim protection. This study aims to systematically examine the regulatory framework for Hajj protection in Indonesia and identify implementation gaps and interrelationships between policies. This study employed a systematic literature identification and mapping approach based on Scopus-indexed publications for the 2019–2024 period, analyzed through qualitative synthesis and concept mapping. The results indicate that Hajj protection in Indonesia is regulated through a multi-layered framework encompassing ministerial regulations, national laws, and institutional arrangements, particularly PMA Number 29 of 2015 and Law Number 8 of 2019. However, the findings also reveal significant gaps in implementation, including limitations in controlling repeat Hajj pilgrimages, weak institutional coordination, a lack of transparency in the management of Hajj funds by the Hajj Fund Management Agency, and inconsistencies in oversight and compliance with health standards. The study concludes that strengthening regulations, increasing oversight, and developing public awareness are key strategies to improve the effectiveness of Hajj protection.